Duration of intracapsular development of Zidona dufresnei (Gastropoda: Volutidae) at its southern distributional limit - Roche, Andrea (2013)
Zidona dufresnei Donovan, 1823 is an endemic snail of the southwestern Atlantic Ocean. In San Antonio Bay, Río Negro Province, it is commonly found in the intertidal zone all year round and from October to April the females deposit planoconvex egg capsules attached to hard substrates. The population of Z. dufresnei studied is an exception because it is unique in that inhabits shallow waters. The main goal of this study was to determine the duration of the direct intracapsular development of Z. dufresnei in the fi eld. Results show that the intracapsular development takes 34.5 ± 3.8 days. In late developmental stages, a mean of three embryos per capsule was observed. Developmental duration under natural conditions was shorter than in lab conditions previously studied. The shorter developmental period than that reported for other temperate neogastropods may be related to the high summer water temperatures and high salinity at the location studied. Shorter embryonic duration would be important for this population of Z. dufresnei which inhabits an environment of high predation pressure on egg capsules.